Ulgi podatkowe jako element pomocy publicznej udzielonej przedsiębiorcom przez gminy w Polsce w latach 2002-2004 - Rękas, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Gmina is a local authority that through the application of tax allowances can create a favourableenvironment for starling up and developing a business activity, thus making the location attractive tobusiness. The awarding of tax allowances by gminas is regulated by the national laws on public aidand strictly controlled by the EU laws. This means that the lax allowances should be assessed againstthe background of size, forms, and targets of public aid.The article attempts to analyse the level of public aid offered to businesses in Poland, in particularthe aid provided by gminas in the form of tax allowances during the 2002-2004 period, as wellas to evaluate the impact of the public aid offered by gminas on market competition. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 21-31